Cataloguing and Interlibrary Loan - Pavlovic, Aleksandra (Infotheca - Journal for Digital Humanities, 2024)
As a part of the 69th International IFLA Conference, that was held in Berlin (1-9 August 2003), two days had sessions devoted to the actual questions and problems of the Interlibrary Loan and Document Delivery.